Pengaruh Kualitas Pelayanan, E Wom, dan Pengalaman Konsumen Terhadap Keputusan Pembelian: Studi Pada Konsumen Facebook Marketplace Kediri - Saputra, Wisnu Adi; Wahyu K, Brahma; Harianto, Kukuh (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to determine the effect of service quality (X1), electronic word of mouth (e-WOM) (X2), and consumer experience (X3) on purchasing decisions (Y) among consumers of Facebook Marketplace in Kediri. This research is a quantitative study processed using statistical methods. The data collection techniques used were primary and secondary data. The sampling technique employed was incidental sampling, with a total sample of 96 respondents. The research data were obtained through questionnaires, literature studies, and documentation. The analytical techniques used include validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and the coefficient of determination test. The results of the multiple linear regression analysis yielded the equation:Y = 5.686 + 0.191X1 + 0.242X2 + 0.425X3 + e. The t-test results showed that the service quality variable obtained a t-value of 2.215 with a significance level of 0.029, the e-WOM variable obtained a t-value of 2.072 with a significance level of 0.041, and the consumer experience variable obtained a t-value of 4.557 with a significance level of 0.000. The F-test results showed an F-value of 39.217 with a significance level of 0.000. Based on these results, it can be concluded that there is a partial effect of service quality on purchasing decisions, e-WOM on purchasing decisions, and consumer experience on purchasing decisions. Moreover, there is a simultaneous influence of service quality, e-WOM, and consumer experience on purchasing decisions.